PENGEMBANGAN MEDIA KARTU ACA PADA MATERI AKSARA JAWA PADA SISWA KELAS 3 SDN 1 SUKOSONO - Safitri, Dian; Wiranti, Dwiana Asih; Zumrotun, Erna (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2024)
One of the challenges for students to maintain their own culture is their lack of understanding of Javanese script. Java has diverse ethnicities, cultures and languages, and these differences create a unique beauty. The method applied in class 3 of SDN 1 Sukosono in this research is the research and development (R&D) method. Researchers applied the ADDIE model which includes 5 phases namely analysis, design, development, implementation, and evaluation. The purpose of this research is to develop ACA Card learning media for Javanese script material and improve students' knowledge in understanding Javanese script. Based on the needs analysis, students have difficulty in understanding Javanese script, especially Carakan script. The results showed that ACA Card media that compiled sentences into cards and used attractive designs obtained validation results from material experts as much as 80% and from media experts as much as 75% with a percentage of decent categories. The ACACard media trial showed an increase in scores from pretest 53.87 to posttest 81.00 for 15 students. The results of the analysis test with paired sample t-tests on SPSS 26 show a significance value (2-tailed) of 0.000 <0.05, which means that there is a difference in the average acquisition of learning outcomes before and after the application of ACA Card media in Javanese script learning in elementary schools. Thus, the development of ACA Card media can be concluded to be effective for developing students' understanding of Javanese script material, especially Carakan script.